Digital transformation: a comprehensive evaluation of organizational impact / Nor Famiza Tarsik - Tarsik, Nor Famiza (Universiti Teknologi MARA, Kedah, 2024)
The term "digital transformation" describes the process of incorporating digital technologies into every facet of an organization's operations, thereby transforming how they function and provide value to their clients. According to Kraus et al. (2021), digital transformation is no longer just a technology solution but it has become an absolute necessity to meet the demands and expectations of a rapidly expanding global population.